Could neutrophil-to-lymphocyte ratio be a new mortality predictor value in severe burns? - Ali Ciftci; Osman Esen; M Burc Yazicioglu; M Celalettin Haksal; Cagri Tiryaki; Abdullah Gunes; Osman Civil; Mehmet Ozyildiz; Hayrunisa Esen (Journal of Surgery and Surgical Research - Peertechz Publications, 2019)
Background: The aim of our study was to demonstrate if there is any relation between the neutrophil-to-lymphocyte ratio (NLR) and mortality in severe burns. Methods: The records of 366 patients who were admitted to Intensive Care Unit of Burn Center of Derince Training and Research Hospital between January 2012 and December 2015 were evaluated retrospectively. The cases who were hospitalized in service or did not require intensive care were not included in the study. The cases were divided into two groups: ex-group (Group 1) and discharge group (Group 2). In both groups demographic information such as age, gender, burn scores, neutrophil counts and lymphocyte counts during admission to the hospital were recorded. NLR is the ratio of absolute neutrophil count to the absolute lymphocyte count. Results: NLR was 10.94±7.63 in the exitus group and 5.5±5.56 in the discharged group. NLR was increased in mortality group and this value was statistically significant (p=0.00). Independent relationship between prognoses and NLR was shown with logistic regression analyses (Odds Ratio 0.895, 95% confidence interval 0.856-0.936, p=0.00) Conclusion: NLR has increased in mortality group. Our study showed that NLR is correlated with probability of mortality after severe burn injuries. Therefore, it can be used as a cheap, easily obtained and new mortality predictor in severe burns.